Case Method Based E-Module: History Learning Innovation to Improve Students’s Higher Order Thinking Skills - Wahyuni, Anny; Saputra, Muhammad Adi; Kurniawanti, Merci Robbi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The low reading literacy of history students has an impact on the low level of Higher Order Thinking Skills they have, especially in the scientific field. Therefore, an innovation is needed in learning history by digitizing learning resources through e-modules based on case method. This research aims to produce case method-based e-modules in improving students' higher order thinking skills and determine the feasibility of the developed e-modules. This research is a type of Research and Development (R&D) research using the ADDIE model which consists of the stages of analyze, design, develop, implementation, and evaluation. The developed e-module was validated by a team of media experts and material experts. The results obtained are that the e-module is suitable for large group tests and small group tests. The small group test got a percentage of 85% and the large group test got a percentage of 77%. Based on these results, it shows that this case method-based e-module is very feasible to be used as a learning resource for students in the history of the entry of Hindu-Buddhist religions into Indonesia in terms of design, content, videos, case studies and practice questions in the e-module and this e-module is effectively used as a learning resource after the T test.